Sound Generation by a Centrifugal Volute Pump at Blade Pass Frequency - Morgenrotn, Michael (My University, 1995)
The behaviour of a centrifugal volute pump as a source of pressure pulsations as well as the role that the pump-pipeline interaction plays in the amplification of these pressure pulsations were experimentally investigated.
A test apparatus was designed and built which features acoustic tuning by pump shaft speed control, dynamic pressure measurements at different locations of the system and qualitative flow visualization capabilities.
A semi-empirical model based on a combination of a Green's function solution for the one-dimensional acoustic boundary value problem and a decay function, corresponding to the break down of large cortex structures in the cascade of turbulence, was developed to separate pressure pulsations of acoustic and hydraulic nature.
Flow visualization in the acoustic near field around the pump's cut-water region was correlated with the acoustic pressure pulsations. A study, parametric in Helmholtz number, relative pump flow rate and cut-water tip radius, was conducted.
Results pertain to the acoustic behaviour of a pump in a piping system:
The pump acts primarily as a pressure source that may be acoustically reflective or transparent depending on the prevailing flow conditions. The near field shows pulsing flow separation which occurs on either side of the cut -water depending on relative flow rate. For cut-water geometries with a clear separation point (sharp tip), a strong sound generation dependence on the relative flow is displayed. A well defined point of flow separation at the cut-water tip leads to the largest separation region and also the largest acoustic pressure pulsations. Rounding the cut-water has the effect to permit motion of the stagnation point, thereby reducing the size of the separation region as well as the acoustic pressure pulsations. Clearly, the geometrical details of the cut-water region play a significant role for sound generation without obvious changes in hydraulic performance.
Keywords: Mechanical Engineering; Mechanical Engineering